1971
DOI: 10.1113/jphysiol.1971.sp009477
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to tilting in tetraplegic man

Abstract: SUMMARY1. A study has been made of the effect of head-up tilt on blood pressure, heart rate, forearm blood flow and occluded vein pressure in the hand and foot in non-bedridden patients with chronic, closed, complete, localized traumatic transaction of the cervical spinal cord.2. In typical responses the blood pressure fell and the heart rate rose progressively for about 2 min, tending to plateau thereafter. The average falls in mean blood pressure for tilts of + 30, + 45 and + 600 were from 68 to 44, 74 to 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Orthostatic hypotension is a common occurrence following SCI, and in some tetraplegic patients this may significantly extend their rehabilitation periods 1) . The symptoms of hypotension are the result of inadequate perfusion of the central nervous system as a consequence of the sudden fall in BP %HR shows actual maximum heart rate as a percentage of expected maximum heart rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthostatic hypotension is a common occurrence following SCI, and in some tetraplegic patients this may significantly extend their rehabilitation periods 1) . The symptoms of hypotension are the result of inadequate perfusion of the central nervous system as a consequence of the sudden fall in BP %HR shows actual maximum heart rate as a percentage of expected maximum heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of OH is complex and involve the cardiovascular, the renal, the neurological and the endocrine systems, all of which are necessary for the regulation of arterial blood pressure [1][2][3] . The symptoms associated with OH significantly interfere with the rehabilitation of patients with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the key ones were: Johnson et al 18 on orthostatic hypotension and the renin-angiotensin system in Paraplegia, three papers in the Journal of Physiology on cardiovascular reflex response to cutaneous and visceral stimuli in spinal man, cardiovascular changes associated with skeletal muscle spasm in tetraplegic man and cardiovascular responses to tilting in tetraplegic man [19][20][21] and one in Lancet on the evidence for neurogenic control of cerebral circulation. 22 For many years we have had a close collaboration with Chris Mathias and his co-workers, key contributions being 'Blood pressure plasma catecholomines and prostaglandins during artificial erection in tetraplegic man' , 23 'Plasma prostaglandin E during neurogenic hypertension in tetraplegic man' , 24 'Enhanced pressor response to noradrenaline in patients with cervical spinal cord transection' , 25 'Renin release during head-up tilt occurs independently of sympathetic nervous activity in tetraplegic man' , 26 and a chapter in the Handbook of Clinical Neurology 'The cardiovascular system in tetraplegia and paraplegia' .…”
Section: Cardiovascular Phenomenamentioning
confidence: 99%
“…(2) A modest and delayed release of catecholamines already at a low resting level 10,13,14 triggering o the renin-angiotensin system by the renal baroreceptors 11,13,14 (3) Then, in the absence of a su cient correction of the OH, a release of ADH and eventually the onset of secondary hyponatraemia. 15 ± 18,20 It has also been shown that the osmoregulatory system functions normally in spinal injured patients and that hypokalaemia, more pronounced in those who are tetraplegic, co-exists with an increase of the volume of extra-cellular¯uids and unstable hyponatraemia.…”
mentioning
confidence: 99%